The Indispensability of Peaceful Coexistence to The Attainment of SDGs In Northern Nigeria: Excerpt From The Biography of Prophet Muhammad (PBUH) - Ammaru Ummaru; Mohd Farid Mohd Sharif (CV. FOUNDAE, 2025)
Islam views peace and harmony as basic tools for the achievement of any developmental goals be it mundane or spiritual and, conversely, sees chaos as an enemy to progress. Hence, it condemned crises in stronger terms and encouraged peaceful coexistence. As such, peaceful co-existence was one of the top priorities of Prophet Muhammad, Peace be Upon Him (PBUH) before he becomes a Prophet, during the early period of his call in Makkah and throughout his life in Madinah. As such, one of the major factors that led to the achievement of sustainable development in the fields of economy, education, governance, environment and social welfare in the nascent state of Madinah was the peaceful co-existence among diverse religious followers and tribes under the leadership of Prophet Muhammad PBUH. The Muslim-dominated region of Northern Nigeria has been and is still experiencing a series of ethno-religious conflicts and bitterest relations between Christians and Muslims. This resulted in mass destruction of lives and properties, hatred, mistrust, lack of cooperation and recurrence conflicts between the two faithful with adverse repercussions of insecurity, underdevelopment and stagnation in the fields of economy, education, and social life. This paper is an attempt to showcase the indispensability of peaceful co-existence to the actualization of Sustainable Development Goals (SDGs) in Northern Nigeria, taking the lifestyle of Prophet Muhammad PBUH as a model. The researcher used analytical method by using secondary data in conducting the research. The findings of the paper revealed the necessity of peaceful co-existence between Muslims and Christians, and among the diverse ethnic groups for the attainment of SDGs in the region. It, therefore, recommends the application of Prophet Muhammad’s PBUH proactive measures of promoting peaceful coexistence for the restoration of peace and harmony in the region.